Garment lifethreads / Hasdiza Dalila Abu Hassan - Abu Hassan, Hasdiza Dalila (Universiti Teknologi MARA, Kedah, 2025)
Garment LifeThreads (GLT) is an innovative clothing capsule designed specifically for NGOs to efficiently distribute garments to disaster victims, including flood victims in evacuation centers. It addresses the critical need for organized, protected, and accessible clothing during crises such as floods and landslides, where victims often lose their belongings and require immediate access to clean, warm, and durable clothing for comfort and dignity. GLT features a compact and lightweight design, making it easy to distribute and handle during relief operations. Constructed with weather-resistant materials, it ensures garments remain protected and suitable for harsh environments, extending their usability even in challenging conditions. The capsule’s modular organization enables quick access to clothing for diverse age groups and genders, ensuring inclusivity and practicality in emergency settings. This innovative solution bridges gaps in traditional clothing distribution methods by combining functionality, durability, and accessibility. GLT empowers NGOs to provide swift and effective relief to disaster victims, especially flood victims in evacuation centers, while restoring dignity and comfort. It sets a new benchmark for efficient and compassionate humanitarian aid.